2021
DOI: 10.7717/peerj.12351
|View full text |Cite
|
Sign up to set email alerts
|

Removal or component reversal of local geomagnetic field affects foraging orientation preference in migratory insect brown planthopper Nilaparvata lugens

Abstract: Background Migratory brown planthopper Nilaparvata lugens (N. lugens) annually migrates to Northeast Asia in spring and returns to Southeast Asia in autumn. However, mechanisms for orientation and navigation during their flight remain largely unknown. The geomagnetic field (GMF) is an important source of directional information for animals (including N. lugens), yet the magnetic compass involved has not been fully identified. Methods Here we assessed the influences of GMF on the foraging orientation preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…21 Subsequent investigations disclosed that CRYs interact with IscA1 (an analog of bacterial iron-sulfur cluster assembly) and exhibit coordinated responses to external magnetic fields, influencing foraging orientation preferences in migratory macropterous BPH. 22,23 This phenomenon bears resemblance to the light-dependent magnetic sensing function of CRYs in D. melanogaster and D. plexippus. 24,25 Even so, however, remarkably little is known about other physiological processes in BPH that might be regulated by crys and/or by the circadian clock.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…21 Subsequent investigations disclosed that CRYs interact with IscA1 (an analog of bacterial iron-sulfur cluster assembly) and exhibit coordinated responses to external magnetic fields, influencing foraging orientation preferences in migratory macropterous BPH. 22,23 This phenomenon bears resemblance to the light-dependent magnetic sensing function of CRYs in D. melanogaster and D. plexippus. 24,25 Even so, however, remarkably little is known about other physiological processes in BPH that might be regulated by crys and/or by the circadian clock.…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, a putative relationship between NlCRYs' functionality and migration dynamics has been documented in the wing‐dimorphic BPH 21 . Subsequent investigations disclosed that CRYs interact with IscA1 (an analog of bacterial iron–sulfur cluster assembly) and exhibit coordinated responses to external magnetic fields, influencing foraging orientation preferences in migratory macropterous BPH 22,23 . This phenomenon bears resemblance to the light‐dependent magnetic sensing function of CRYs in D. melanogaster and D. plexippus 24,25 .…”
Section: Introductionmentioning
confidence: 94%
“…The geomagnetic field has been found [15] to be an important source of directional information for animals (including Nilaparvata lugens Stål, 1854), but the relevant magnetic compass has not yet been fully identified. They found that the near-zero magnetic field or vertical reversal of geomagnetic field could lead to Brown Planthopper (Nilaparvata lugens) losing the foraging orientation preference, suggesting that a normal level of GMF, in the way of either intensity or inclination, was essential for the foraging orientation of Brown Planthopper.…”
Section: Pheromone Trap Catch Of Fruit Pest Moths Influenced By the G...mentioning
confidence: 99%
“…As a highly conserved A-type iron-sulfur protein, IscA has been proposed as a magnetoreceptor renamed MagR [ 15 , 33 ], which has also been suggested to influence circadian rhythms in Drosophila [ 34 ]. Research into MagR’s role in magnetoresponse and its potential applications is expanding [ 16 , 25 , 26 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Although no protein interactions between MagR and Cry were observed in the European robin, Erithacus rubecula [ 50 ], a well-known migrant bird species, such interactions have been identified in other vertebrates and invertebrates.…”
Section: Introductionmentioning
confidence: 99%